2013
DOI: 10.1097/ta.0b013e318282747a
|View full text |Cite
|
Sign up to set email alerts
|

Venous and arterial base deficits

Abstract: Diagnostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…These modifications were deemed negligible and the authors concluded that the techniques were equivalent. Very good agreement between arterial and venous measurements of base deficit was also found in trauma patients [9, 10]. Similar results, with a mean pH difference of 0.03 [95% CI − 0.02 to 0.08], were found in critically ill patients with metabolic acidosis of various causes, except ketoacidosis [11].…”
Section: Areas Of Recommendationssupporting
confidence: 58%
“…These modifications were deemed negligible and the authors concluded that the techniques were equivalent. Very good agreement between arterial and venous measurements of base deficit was also found in trauma patients [9, 10]. Similar results, with a mean pH difference of 0.03 [95% CI − 0.02 to 0.08], were found in critically ill patients with metabolic acidosis of various causes, except ketoacidosis [11].…”
Section: Areas Of Recommendationssupporting
confidence: 58%
“…Second, the validation based on blood gas parameters and lactate level taken from arterial or venous blood was not evidence based. According to the result of recent articles [28–30, 36] venous and arterial pH and bicarbonate agree reasonably well at all values and the lactate level showed a poorer agreement only at abnormal values. This was the scientific background using arterial or venous samples.…”
Section: Discussionmentioning
confidence: 77%
“…This parameter combination has never been used previously, but as individual parameters they have an important role to play in the evaluation of the patient’s status. The pH and BE values from the blood gas sample and the lactate levels are strongly related in both arterial and venous blood so we can use samples from either origin [28–30]. These three parameters represent a summary of the pathophysiological processes and are independent of our examined categories.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of victims trapped in disasters die immediately due to serious injuries, while 10% suffer minor trauma and another 10% suffer crush injuries. [4][5][6]15] MacKenzie et al [16] conducted a study revealing that 87% of the injuries requiring medical attention following an earthquake were orthopedic injuries. Furthermore, their research indicated that the incidence of rhabdomyolysis in critically ill patients was found to be 36.2%.…”
Section: Discussionmentioning
confidence: 99%